Sejarah Perkembangan Asuransi Syariah di Korea Selatan - Insulindeyuliyati (CV. Kalimasada Group, 2023)
The purpose of this study is that the author wants to know the history of the development of Islamic insurance in Korea. We all know that Korea is a country where the majority of the population adheres to non-Muslim religions. The methodology used in this research is literature. The author chooses secondary data from various sources, namely. books and literature reviews from previous researchers discussing the same topic. With respect to the results of this study indicate that Korea is a country with 31.6% Christian (Catholic and Protestant), 24.2% Buddhist and 43.3% have no religion. concluded that Muslims belong to the minority category in this country. It is very difficult to develop Islamic insurance in Korea due to many factors, namely Muslims are a minority and there is a strong culture that makes it difficult for them to introduce new Islamic insurance products. Korean society has not reached a sufficient understanding of Islamic insurance.